2012
DOI: 10.1007/s10526-012-9470-2
|View full text |Cite
|
Sign up to set email alerts
|

Intraguild predation between the invasive ladybird Harmonia axyridis and non-target European coccinellid species

Abstract: The coccinellid Harmonia axyridis (Pallas) has been used for augmentative and classical biological control in many environments. More recently it has invaded large parts of Europe and negative effects for native populations of aphidophagous coccinellids are beginning to emerge. Here we investigate intraguild predation (IGP) between H. axyridis and eleven native non-target European coccinellids, including less common species which have not been studied so far within this context of non-target effects. When firs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 60 publications
(75 reference statements)
3
75
0
1
Order By: Relevance
“…These features seem to result in unidirectional IGP for encounters between H. axyridis and A. ocellata in which the latter dominates. The importance of spiny larval projections for anti-predator defence and probability to win in intraguild confrontation was further demonstrated by Ware and Majerus (2008) and Katsanis et al (2013). They found that spiny larvae of other ladybird species, such as Calvia quatuordeciguttata (L.) or Harmonia quadripunctata (Pontoppidan), although often preyed upon by larvae of H. axyridis, relatively frequently played a role of intraguild predators of the latter.…”
Section: Intraguild Predatorsmentioning
confidence: 95%
See 2 more Smart Citations
“…These features seem to result in unidirectional IGP for encounters between H. axyridis and A. ocellata in which the latter dominates. The importance of spiny larval projections for anti-predator defence and probability to win in intraguild confrontation was further demonstrated by Ware and Majerus (2008) and Katsanis et al (2013). They found that spiny larvae of other ladybird species, such as Calvia quatuordeciguttata (L.) or Harmonia quadripunctata (Pontoppidan), although often preyed upon by larvae of H. axyridis, relatively frequently played a role of intraguild predators of the latter.…”
Section: Intraguild Predatorsmentioning
confidence: 95%
“…Yasuda and Ohnuma 1999;Yasuda et al 2004;Pell et al 2008;Ware and Majerus 2008;Raak-van den Berg et al 2012), little data is available on H. axyridis as an intraguild prey. Indeed, in experiments testing the outcomes of intraguild interactions involving H. axyridis, it usually appears superior to other aphidophagous predators (Yasuda and Ohnuma 1999;Yasuda et al 2004;Ware and Majerus 2008;Raak-van den Berg et al 2012; Katsanis et al 2013). A few exceptions include larvae of the ladybird Anatis ocellata (L.) Katsanis et al 2013) and of the lacewings Chrysoperla carnea (Stephens) (Nedvȇd et al 2010(Nedvȇd et al , 2013 and C. rufilabris (Burmeister) (Michaud and Grant 2003).…”
Section: Intraguild Predatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, no H. axyridis has been recorded in maize and alfalfa (two crops where coccinellids are abundant) and this suggests that the invasion of the Asian ladybeetle is recent. However, the invasion of crop fields should be promptly observed, as has happened in other countries, and all these three native coccinellids species are showed to be in disadvantage intraguild predation experiments with H. axyridis Lucas, 2012;Katsanis et al, 2013).…”
Section: What Is the Phenology Of The Establishment And Spreading Of mentioning
confidence: 97%
“…Ceryngier et al (2004) showed that females of some coccinellid species may have inactive ovaries in early dormancy but sperm in their spermatheca, facilitating an early fertilization process in overwintering sites or nearby them. The lower weight loss in females than in males in the Les Llosses's aggregation may be an indicator that females started their 8 Katsanis et al, 2013), negative impact on them should be expected also in urban landscapes. In Eastern Canada, A. bipunctata has disappeared from urban landscapes since the arrival of H. axyridis (Lucas, pers.…”
Section: What Is the Phenology Of The Establishment And Spreading Of mentioning
confidence: 97%